Differences of Urine Glucose in Diabetic Mellitus with and without Toluene Preservative based on Temperature Variations and Storage Time - Afshari, Kety Fiqih; Mustaming, Mustaming; Anggrieni, Nurul (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine the difference in urine glucose of Diabetes Mellitus patients with and without toluene preservative based on variations in temperature and storage time. Methods This research is descriptive comparative with the purposive sampling technique which was carried out on 34 urine samples of outpatient Diabetes Mellitus patients at the Inche Abdoel Moeis Samarinda Hospital which were analyzed at the Clinical Chemistry Laboratory of the Poltekkes Kaltim using the strip method on a urine analyzer with the Mann Whitney statistical test. Univariately, urine glucose levels 2+ were immediately found in 13 (38%) and 3+ in 21 (62%) samples, urine glucose levels 2+ delayed with toluene preservative stored at room temperature for 4 hours and 8 hours, respectively, obtained 15 (44%) and 18(53%) samples, as well 19(56%) and 16(47%) samples with a grade of 3+. Toluene stored at room temperature (25°C) and refrigeration in the refrigerator (4°C) without preservatives can be an alternative as a preservative for urine glucose testing if the examination cannot be done immediately.